Empathy and Helping Behavior in Adolescence: The Role of Parent-Child Relationships. - Buckingham, Mary. (2017)
Abstract: Relations between parent-child relationship qualities and empathy and helping behavior are important to consider in adolescence, given that both change and stability occur in the parent-adolescent relationship during this time. The role of circular functions in the parent child relationship is informed by a relational developmental systems theories (RDST) approach to understanding human development. These theoretical perspectives suggest that characteristics of individuals promote differential actions in socializing others and provide feedback to the person, affecting his or her future individual development. Consistent with such relations, researchers have found positive associations between parent-child relationship qualities and child empathy and, as well, prosocial behavior. In order to elucidate the complexities of the parent child relationship in promoting empathy development and begin to investigate how empathy and helping behavior develop within a RDST model of parent-child relationships, this research used data from Grades 5 and 9 of the 4-H Study of Positive Youth Development to examine if adolescents' perceived maternal warmth and family connection differentially predict empathy and helping behavior. Results indicated that perceived maternal warmth and family connection did not predict empathy or helping behavior. However, empathy did predict adolescents' helping behavior. The results and limitations of this study are discussed and suggestions for future research are made.; Thesis (M.A.)--Tufts University, 2014.; Submitted to the Dept. of Child Development.; Advisor: Richard Lerner.; Committee: Lacey Hilliard, and Megan Mueller.; Keyword: Developmental psychology.